Current status of umbilical cord blood transplantation in children. (13th August 2019) - Gabelli, Maria; Veys, Paul; Chiesa, Robert
Summary: The first umbilical cord blood (UCB) transplantation was performed 30 years ago. UCB transplantation (UCBT) is now widely used in children with malignant and non‐malignant disorders who lack a matched family donor. UCBT affords a lower incidence of graft‐ versus ‐host disease compared to alternative stem cell sources, but also presents a slower immune recovery and a high risk of infections if serotherapy is not omitted or targeted within the conditioning regimen. The selection of UCB units with high cell content and good human leucocyte antigen match is essential to improve the outcome. Techniques, such as double UCBT, ex vivo stem cell expansion and intra‐bone injection of UCB, have improved cord blood engraftment, but clinical benefit remains to be demonstrated. Cell therapies derived from UCB are under evaluation as potential novel strategies to reduce relapse and viral infections following transplantation. In recent years, improvements within haploidentical transplantation have reduced the overall use of UCBT as an alternative stem cell source; however, each may have its relative merits and disadvantages and tailored use of these alternative stem cell sources may be the optimal approach.